The function of p53 and its role in Alzheimer’s and Parkinson’s disease compared to age-related macular degeneration - Wolfrum, Peter; Fietz, Agnes; Schnichels, Sven; Hurst, José (Frontiers in Neuroscience, 2022)
The protein p53 is the main human tumor suppressor. Since its discovery, extensive research has been conducted, which led to the general assumption that the purview of p53 is also essential for additional functions, apart from the prevention of carcinogenesis. In response to cellular stress and DNA damages, p53 constitutes the key point for the induction of various regulatory processes, determining whether the cell induces cell cycle arrest and DNA repair mechanisms or otherwise cell death. As an implication, aberrations from its normal functioning can lead to pathogeneses. To this day, neurodegenerative diseases are considered difficult to treat, which arises from the fact that in general the underlying pathological mechanisms are not well understood. Current research on brain and retina-related neurodegenerative disorders suggests that p53 plays an essential role in the progression of these conditions as well. In this review, we therefore compare the role and similarities of the tumor suppressor protein p53 in the pathogenesis of Alzheimer’s (AD) and Parkinson’s disease (PD), two of the most prevalent neurological diseases, to the age-related macular degeneration (AMD) which is among the most common forms of retinal degeneration.